2009
DOI: 10.1177/0363546509346542
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Findings and Possible Causes of Osteochondritis Dissecans of the Knee

Abstract: The results of this histologic study provide readers with several insights about the causes and treatment options of osteochondritis dissecans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(120 citation statements)
references
References 26 publications
8
108
2
2
Order By: Relevance
“…However, Yonetani et al [84] found no osseous necrosis on microscopic examination in biopsy samples obtained from intact OCD lesions. Furthermore, Uozumi et al [78] demonstrated an absence of subchondral bone in six of 11 biopsy samples and of the remaining five specimens with an osseous component, only two demonstrated no viable osteocytes. Therefore, it seems the necrosis found in OCD may be secondary to the actual detachment of the lesion rather than the underlying etiology of formation.…”
Section: Etiologymentioning
confidence: 99%
“…However, Yonetani et al [84] found no osseous necrosis on microscopic examination in biopsy samples obtained from intact OCD lesions. Furthermore, Uozumi et al [78] demonstrated an absence of subchondral bone in six of 11 biopsy samples and of the remaining five specimens with an osseous component, only two demonstrated no viable osteocytes. Therefore, it seems the necrosis found in OCD may be secondary to the actual detachment of the lesion rather than the underlying etiology of formation.…”
Section: Etiologymentioning
confidence: 99%
“…The form that is most similar to osteochondrosis dissecans in animals is the juvenile form. 23,58,67 Degenerated chondrocytes were found in excised cylinders and fragments from the elbow joint of 10-to 16-year-old patients 56 Retained cartilage a found in excised cylinders and fragments from the medial femoral condyle of 12-to 22-year-old patients 112 Retained cartilage a found in excised cylinders from the medial femoral condyle of 12-to 15-year-old patients 128 …”
Section: Causes Of Vascular Failurementioning
confidence: 99%
“…Of the 11 studies, four used formalin (varying concentrations) [10,14,28,31], one study each used formaldehyde 10% [4] or alcohol [20], and five did not report a fixation agent [3,8,9,16,30]. Decalcification agents used among the studies varied: one study used 5% nitric acid and 70% alcohol [4], one study used 40% formic acid and 20% sodium citrate [14], one study used EDTA [28], one study reported that no decalcification was used [20], and seven did not report on decalcification [3, 8-10, 16, 30, 31]. For histological analysis, six separate stains/analyses were used with varying frequency (Table 1).…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
“…For histological analysis, six separate stains/analyses were used with varying frequency (Table 1). Six studies used hematoxylin and eosin [4,14,16,28,30,31], two used Safranin-O (one in combination with Fast-Green) [14,31], one used toluidine blue [14], one used Alcian blue [10], one study used von Kossa stain [10], one study used Gomori trichrome stain [10], and one study used Goldner stain [14]. Two studies preoperatively labeled with tetracycline [14,20] and three studies did not use any staining techniques and only observed crosssections through photomicrographs [3,8,9].…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
See 1 more Smart Citation